Colour and silent racism. Issue 3 (6th December 2012) - Alfredson, Anna; Desai, Dipti
In this article we examine the racialized silence by whites, locating its emergence in history, examining whiteness and pointing to ways that we can begin to address the social context of colour in art education in both K-12 and teacher preparation programmes. Drawing on our experiences teaching in both high school and university classrooms, we argue that this silence by white people is an important component of race talk and that we need to focus on developing racial literacy among our students as one important pedagogical model in art classrooms.